Effect of recombinant human erythropoietin and its combination with tamoxifen on viability of MCF-7 cell in three-dimensional culture - Shujaaedin, Hareth Yahya Ahmed (2019)
Anemia is often a side-effect of cancers. Erythropoietin (EPO) is the erythropoiesisstimulating hormone produced by the kidneys that is used in the treatment of anemias. This hormone is being used concurrently with chemotherapeutic drugs in the treatment of cancers. From previous studies, EPO alone or combined with cancer therapeutics showed inconsistent effects on cancer cells viability in the two-dimensional (2D) cell cultures. Unlike in 2D cell cultures, the effects of drugs on three-dimensional (3D) cell cultures mimic their effects on live tissues. Currently, there is no study that determined the effect of EPO alone or combined with tamoxifens on MCF-7 cell in 3D cultures (spheroids). Thus, the general objective of the study was to determine the effect of recombinant human EPO (rHuEPO) alone and in combination with tamoxifen (rHuEPO-tamoxifen combination) on the viability of MCF-7 breast cancer cell spheroids. The specific objectives of the study were to generate stable in vitro MCF-7 spheroids, determine the effects of rHuEPO and rHuEPO-tamoxifen combination treatments on the viability and MCF-7 cell cycle phase of the spheroids. MCF-7 cells were grown in monolayer culture until 85 % confluency was reached. Then, the MCF-7 spheroids were generated by the conventional hanging drop (CHD) combined ultra-low adhesive plate (ULAT). The MCF-7 spheroids were then treated with 0.1, 3.12, 6.25, 10, 12.5, 25, 50, 100, and 200 IU/mL rHuEPO, 10 μg/mL (IC50) tamoxifen, or 10 μg/mL tamoxifen in combination with 10, 100 or 200 IU/mL rHuEPO for 24, 48 or 72 h. The effects of rHuEPO and combination rHuEPO-tamoxifen treatments on MCF-7 spheroids were determined using the (4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay, neutral red retention, trypan blue exclusion assay, DNA fragmentation, acridine orange/propidium iodide staining, caspases activation assays, and cell cycle assay and flow cytometry analyses after staining with propidium iodide. Treatment with rHuEPO, at high concentrations of 10, 50, 100, and 200 IU/mL decreased cell viability and (p<0.05) caspase-3, -8, or -9 activities in the MCF-7 spheroids in dose-dependent manner. Treatment with rHuEPO alone increased the population of MCF-7 cells in the subG1/G0 phase also in dose- and time-dependent manner. Based on the annexin-V and cell cycle assays, tamoxifen and the rHuEPOtamoxifen combination treatments both caused the MCF-7 cells in the spheroids to undergo apoptosis. However, the cytotoxic effect of rHuEPO-tamoxifen combination was more intense than the effect of tamoxifen alone. Although treated cells showed morphological characteristics of apoptosis, the caspase activities were downregulated after rHuEPO-tamoxifen combination treatments, suggesting that the MCF-7 cell death was not associated with caspase activities. In conclusion, the study showed that the antiproliferative effects of rHuEPO toward the MCF-7 cells is via cytostasis. This study also suggests that rHuEPO is not only safe for use with chemotherapeutic drugs to treat cancer-related anemias, but also potentiate the toxic effects of tamoxifen toward breast cancer cells.